Accuracy of colposcopic findings in detecting vaginal intraepithelial neoplasia: a retrospective study - Stuebs, Frederik A.; Koch, Martin; Mehlhorn, Grit; Gaß, Paul; Schulmeyer, Carla; Hartmann, Arndt; Strehl, Johanna; Adler, Werner; Beckmann, Matthias; Renner, Stefan (Archives of Gynecology and Obstetrics, 2020)
Purpose: Malignancies of the vagina are rare, but colposcopy-directed biopsies play a major role in detecting vaginal intraepithelial lesions. Data of accuracy in detecting neoplasia of the vagina are very rare compared to accuracy in detecting cervical neoplasia. The aim of this study was to evaluate the accuracy of colposcopy-directed biopsy in comparison with clinical findings of the examiner. Methods: The accuracy of colposcopy-directed biopsy was compared with the clinical finding in relation to the patient’s age and the examiner’s level of training. This was done in combination with PAP-smear, HPV-test results, and the history of other malignancies of the lower genital tract. The data were collected between January 2014 and February 2018 at the certified Dysplasia Unit of the University Hospital Erlangen. Results: In total, 253 biopsies from 253 women from the vagina were obtained. The overall accuracy of biopsy in comparison with clinical finding was 52.17% for all entities—benign lesions, low-grade squamous intraepithelial lesions (LSILs), high-grade squamous intraepithelial lesions (HSILs), and vaginal carcinoma. The accuracy for detecting HSIL was 82.46% (47/57), with an underdiagnosis rate of 15.79% and an overdiagnosis rate of 1.79%. Conclusion: With a sensitivity of over 80%, colposcopy-directed biopsy plays an important role in detecting vaginal–HSIL. A highly experienced practitioner is increasing the sensitivity in detecting vaginal–HSIL. Careful examination is required in women with a history of HSIL of the lower genital tract or with simultaneous neoplasia because they are of greater risk of developing vaginal malignancies. The combination of careful clinical work up, PAP-smear, HPV-testing, and colposcopy-guided biopsy is crucial in detecting vaginal–HSIL.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Colposcopy-directed biopsy; High-grade squamous intraepithelial lesion (HSIL); Vaginal cancer; Vaginal intraepithelial neoplasia (VaIN)